Fonte ininterrupta de energia trifásica de alto desempenho sem transformador com dupla funcionalidade do estágio de entrada e sistema de controle digital - Venturini, William Alegranci (2016)
This master s thesis proposes a three-phase transformerless double-conversion UPS with digital control system and reduced overall cost. The topology is composed of an input stage, a battery bank, an inverter, an auxiliary circuit and transfer switches. The input stage assumes the three-phase rectifier function with LCL filter in normal operation mode and is responsible for discharge the battery bank in backup mode. This configuration reduces the system cost since an available circuit is used to discharge the battery bank. In conventional double-conversion UPS topologies the input stage remains inactive during the backup mode and an additional circuit is employed for this purpose. The auxiliary circuit is formed by an inductor and a switching leg and is used as a battery charger during normal operation mode and is additionally used to balance the bus capacitors voltages in backup mode. In this configuration, the auxiliary circuit can be designed for only a fraction of the UPS rated power, also providing lower total system cost. Transfer switches change the configuration of the input stage and the auxiliary circuit according to the UPS operating mode. The detailed operation of the topology, modelling, digital control structure, and the results obtained by simulation are showed. Finally a 20 kVA prototype is implemented and experimental results are acquired for the validation of the employed design methodology as well as the proposed circuit functionality.